2018
DOI: 10.4103/ijnmr.ijnmr_77_17
|View full text |Cite
|
Sign up to set email alerts
|

Educational and managerial policy making to reduce workplace violence against nurses: An action research study

Abstract: Background:The level of occupational violence against nurses increases from 68.8 to 98.6 percent, which is a considerable rate among healthcare settings. To create a safe environment for patient care in the emergency department (ED), a comprehensive program for the prevention of violence is necessary. The aim of this study was to plan a workplace violence prevention program (WVPP) to reduce the level of patients' and their families' violence against nurses.Materials and Methods:The present study is a quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 15 publications
(17 reference statements)
0
26
3
Order By: Relevance
“…In conclusion, work-related stressors in Dutch pediatricians are high and can subsequently lead to posttraumatic stress disorder. Parental aggression towards pediatricians seems to be a common problem, something that should be addressed, for example with CMD training programs [19]. In this study, the amount of pediatricians with PTSD complaints was higher compared to prevalences found in the general population and the same applies to depression and anxiety symptoms.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In conclusion, work-related stressors in Dutch pediatricians are high and can subsequently lead to posttraumatic stress disorder. Parental aggression towards pediatricians seems to be a common problem, something that should be addressed, for example with CMD training programs [19]. In this study, the amount of pediatricians with PTSD complaints was higher compared to prevalences found in the general population and the same applies to depression and anxiety symptoms.…”
Section: Discussionmentioning
confidence: 56%
“…Therefore, we think that it is necessary to not only develop a better support system after an adverse event but to also implement ways to teach pediatricians to cope with aggression. For example, certain training programs (conflict management and de-escalation (CMD)) focus on how to cope with aggression [19, 20]. Another stressor may be a complaint to the disciplinary board.…”
Section: Discussionmentioning
confidence: 99%
“…An interventional study from Iran which focused on patient education has reported reduction in the events of violence by 18.6%. 35 Regulatory measures include adherence to access restriction policies of hospitals. Job-related reasons perpetrated by colleagues or seniors included dissatisfaction with performance, being late or disagreeing on job conditions.…”
Section: Bmj Global Healthmentioning
confidence: 99%
“…Likewise, in a study conducted by Warren (2011) to determine Workplace violence in hospitals: Safe havens no more, that majority of nurses who were exposed to workplace violence had various psychological disturbances after the attack. As well, Hemati-Esmaeili et al (2018) mention that the level of occupational violence against nurses increases from 68.8 to 98.6 percent, which is a considerable rate among healthcare settings. Moreover, Magnavita and Heponiemi (2011) concluded that nurses reported more physical assaults during the previous 12 months, and nurses were mostly assaulted or harassed by patients or their relatives and friends.…”
Section: What Is the Level Of Anxiety Regarding Workplace Violence Ammentioning
confidence: 99%
“…Furthermore, the management of violent incidents and its subsequent interventions result in reducing the risk of psychological and physical side effects of violence among nurses. As follows, providing a safe working environment for their employees is the responsibility of healthcare managers (Hemati-Esmaeili et al, 2018). The active participation of managers in policies to prevent and combat violence at work is a preponderant factor for the use of knowledge, skills, and attitudes that allow the appropriate decision making regarding violence management (Sousa et al, 2018).…”
Section: Introductionmentioning
confidence: 99%